Parental reflective functioning: Analysis and promotion of the concept for pediatric nursing - Ordway, Monica Roosa (2014)
AIM: To identify the definitional elements of parental reflective functioning (RF) and develop a framework for nurses to apply this concept in their clinical work with families. Background: In recent years, researchers have concluded that parental RF is a key mechanism in the development of child attachment security leading to lifelong mental and physical health benefits. Despite its clinical relevance, little has been published in the nursing literature on this concept. DESIGN: Concept analysis. METHODS: The Walker and Avant (2011) method of concept analysis and the Whittemore and Knafl (2005) method of integrative review were used. A search of the literature published from 1989 to 2013 was conducted using edited texts and online databases - Scopus, CINAHL, PubMed, and PsychInfo. Among the 85 sources, 31 empirical studies, 17 book chapters, 32 review papers, and 5 case studies were identified concerning parental RF. RESULTS: The concept of RF, defined as the capacity to envision the mental states of self and other, was first described in 1989 by Fonagy. Slade (2005) expanded the concept specifically for parents (i.e. parental RF). Results of this concept analysis describe seven defining attributes and five antecedent conditions. Consequences of parental RF are related to a child’s attachment early in life and behavior later in life. A model case is provided to contextualize the concept. To date, there are three measures for parental RF. CONCLUSIONS: While parental RF has been predominately featured in psychology and parenting interventions, the potential consequences of secure attachment and longer term children’s behavioral outcomes suggest that the concept has global implications for pediatric nurses and primary health care clinicians. RELEVANCE TO CLINICAL PRACTICE: Parental RF offers exciting and promising opportunities for pediatric health and new approaches for those who provide pediatric health care.